Detecção de DNA masculino em amostras de crimes sexuais por PCR em tempo real - Winkler, Cristina (2024)
The insertion of genetic profiles in DNA databases revolutionized the investigation of sexual assault. Before this turning point, it was only possible to investigate cases with known sexual offenders. In Brazil, the use of DNA databases is recent, and, therefore, the processing of samples of cases without a suspect were not considered important until then. For this reason, Brazilian forensic DNA laboratories have a large amount of unanalyzed traces. In this context, increasing the number of genetic profiles inserted into databases can contribute to reducing these backlogs and solving cold cases. However, current DNA analysis practices typically focus on cases where semen is detected. In instances where screening yields negative results, the forensic analysis often concludes and, in most cases, seminal fluid is not detected. Real-time PCR is a technique with high sensitivity and specificity and is already widely used in forensic laboratories. Thus, this project aimed to evaluate the technical feasibility of real-time PCR as a screening method for male fluids in swab samples from women who are victims of sexual assault. After routine testing for semen screening at the Forensic Biology Laboratory of Civil Police of Espírito Santo, 176 swab samples were analyzed using four different qPCR assays. It was performed DNA quantification using a commercial kit with TaqMan probes and three different in house qPCR-duplex reactions with SYBR Green dye. In the DNA quantification assay, among the 84 samples with negative results for semen screening, 39 (46.4%) presented male DNA, a significant proportion often overlooked by most Brazilian forensic laboratories. The three SYBR Green-based qPCR-duplex assays did not show the same sensitivity as DNA quantification with TaqMan probes. This study demonstrated that the use of realtime PCR can be a robust tool for detecting Y DNA as a screening method to identify male contact in cases involving sexual assault.